2008
DOI: 10.1210/me.2008-0010
|View full text |Cite
|
Sign up to set email alerts
|

Nescient Helix-Loop-Helix 2 Interacts with Signal Transducer and Activator of Transcription 3 to Regulate Transcription of Prohormone Convertase 1/3

Abstract: Mechanisms controlling body weight involve gene regulation through the activation of signal transduction pathways. The Janus kinase/signal transducer and activator of transcription (STAT) signal transduction pathway is the mechanism primarily used by leptin in the hypothalamus. The transcription factor nescient helix-loop-helix 2 (Nhlh2) is a downstream target of leptin signaling and is expressed in proopiomelanocortin arcuate neurons. Proopiomelanocortin is cleaved by prohormone convertase 1/3 (PC1/3) to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
(46 reference statements)
1
41
0
Order By: Relevance
“…4b). These findings were of interest because Akt and JAK/STAT signalling are known to activate the expression of Pc1/3 [23, 24]. PC1/3 is required for the processing of proglucagon, the product of the glucagon gene ( Gcg ), to GLP-1 [25].…”
Section: Resultsmentioning
confidence: 99%
“…4b). These findings were of interest because Akt and JAK/STAT signalling are known to activate the expression of Pc1/3 [23, 24]. PC1/3 is required for the processing of proglucagon, the product of the glucagon gene ( Gcg ), to GLP-1 [25].…”
Section: Resultsmentioning
confidence: 99%
“…As we have previously identified key transcriptional targets for Nhlh2 (PC1/3 and Mc4r, for example (Fox and Good, 2008, Wankhade and Good, 2011)), these studies allow us to begin to piece together the molecular pathways between peripheral increases in leptin and hypothalamic control responses. Obesity can result in both high leptin levels and high levels of inflammatory cytokines such as IL6 (Cancello et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…These results identify another Stat3-regulated gene, and as Nhlh2 is itself a transcription factor, identify a mechanism for induction of many possible Nhlh2-regulated target genes. The PC1/3 gene, for example, requires both Nhlh2 and Stat3 to coordinately control its leptin-induced expression (Fox and Good, 2008). Mechanistically, with these results, leptin is now shown to stimulate hypothalamic Stat3, and within the ARC, this leads to transcriptional regulation of POMC, Nhlh2 and, together with newly synthesized Nhlh2, the enzyme needed to process POMC, PC1/3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, it was not clear whether loss of NSCL-2 expression in GnRH neurons is responsible for reduction of GnRH neurons and reduced fertility of Nscl-2 mutants, although it has been demonstrated that NSCL-2 and its close relative, NSCL-1, are concomitantly involved in the control of differentiation and migration of GnRH neurons probably via regulation of necdin expression (Krüger et al, 2004). In response to leptin signaling, NSCL-2 regulates expression of the prohormone convertase 1/3 (PC1/3) in hypothalamic neurons (Fox and Good, 2008), which is required for proteolytic processing of pro-opiomelanocortin (POMC) into ACTH and ␣-melanocytestimulating hormone (␣-MSH). ␣-MSH restricts food intake by signaling via melanocortin-4 receptor (MC4-R) and mediates increased energy expenditure (Elmquist, 2001).…”
Section: Introductionmentioning
confidence: 99%